Think, Pair, Share, and Beyond: Cultivating Critical Thinking via Collaborative Learning in Vocational High Schools - Khalid Al Madani; Tasya Riskiyanti; Putri Nur Kholifatur Rohmah; Tasya Madinah; Izzatul Fajri Ramadani (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The increasing complexity of modern industrial environments has intensified the need for vocational education institutions to cultivate students’ critical thinking skills alongside technical competence. This study aimed to evaluate the implementation of Collaborative Learning through the Think-Pair-Share and Beyond strategy in enhancing students’ critical thinking abilities at SMK Nurul Abror Al Robbaniyin. The research employed a Classroom Action Research design conducted in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through classroom observation, field notes, documentation, and critical thinking assessments focusing on analytical reasoning, evaluation, interpretation, and argumentative communication. The findings revealed a progressive improvement in students’ critical thinking performance and collaborative participation across the research cycles. Students initially demonstrated passive learning behavior and procedural dependence during the pre-cycle stage, but gradually developed stronger analytical engagement, reflective discussion skills, and confidence in communicating technical arguments throughout the intervention process. More substantial improvement emerged during the second cycle following the integration of contextual simulations, visual scaffolding, and guided collaborative reflection within the “Beyond” approach. The study concludes that the modified Think-Pair-Share strategy effectively strengthened critical thinking development and collaborative engagement in vocational classroom learning environments.